Constraints faced by Jhora fish farmers in the Darjeeling Himalayas - Abhilash Thapa; Rama Sharma; Arpita Sharma; Rapden Foning Lepcha (Journal of Indian Fisheries Association, 2023)
Jhora fish farming has been instrumental in supporting income generation for the economically disadvantaged population in the Darjeeling hilly region since 1981. Nonetheless, its effectiveness in this regard has been hampered by several constraints. The primary objective of this study is to identify the constraints faced by Jhora fish farmers that hinder their profitability. A structured interview schedule was used to collect primary data from 120 respondents practicing Jhora fisheries in three types of ponds: cement, mud, and cement with mud bottom. The rank-based quotient (RBQ) method was employed to measure and quantify the technical, environmental, infrastructural, and economic constraints. Results indicated that the most important constraints faced by the Jhora fish farmers were non-availability of quality feed, hatchery, feed mills, predation, and lack of self-finances. Non-parametric Kruskal-Wallis test revealed a significant difference in the median rank scores of eight out of twenty-seven constraints faced by Jhora fish farmers using three types of ponds. Additionally, the study proposed appropriate strategies to augment fish production in the Darjeeling Himalayan hill region, with the aim of popularizing Jhora fisheries among the rural youth.